Wuthering Heights - Trewin, Anna; Brontë, Emily Peck, Hannah (Penguin Books London, 2019)
It is winter in the wild English countryside. A man caught in a snowstorm finds shelter at a remote manor called Wuthering Heights. He learns about Cathy, who lived in the house many years before, whose story is one of love, heartbreak and revenge that still haunts those in the present. Penguin Readers is a series of the best new fiction, essential non-fiction and popular classics written for learners of English as a foreign language. Beautifully illustrated and carefully adapted, the series introduces language learners around the world to the bestselling authors and most compelling content from Penguin Random House. The eight levels of Penguin Readers follow the Common European Framework and include language activities that help readers to develop key skills.Wuthering Heights, a Level 5 Reader, is B1 in the CEFR framework